A argumentação nas redações do Exame Nacional do Ensino Médio: uma análise da (re) produção discursiva da opinião - Preto, Gabriela Mascarenhas Mazaro (2023)
Created in 1998, the National High School Examination (ENEM) is currently a largescale assessment that allows students to enter higher education at many Brazilian universities at the end of basic education. The discursive test is composed of a writing proposal that aims to evaluate the candidate's ability to produce a prose text of the dissertative-argumentative type on a specific topic. This work is part of the line of research “Text and discourse in oral and written modalities”, of the Graduate Program in Portuguese Language at the Pontifical Catholic University of São Paulo and has as its theme the study of argumentation in the essays of the National Examination for its for its argumentative compositional organization to build the candidate's opinion, with the aim of analyzing maximum grade essays to verify the candidate's argumentative/opinionated construction within the text. Thus, the general objective is to contribute to the understanding of the essay-argumentative text in the exam. As for the specific objectives, the following stand out: to analyze the authorial opinionated argumentation of the texts in the discursive formation; verify the argumentative organization of the one or two these in the textual productions of students with a thousand marks, according to the Critical Discourse Analysis under the socio-cognitive aspect, in dialogue with the National Curriculum Parameters of Secondary Education, in order to correlate the argumentation and the discourse. The theoretical foundation lies in Textual Linguistics (Bunzen, 2006; Antunes, 2006, 2009; Marcuschi 2008; Koch, 2011; Koch; Travaglia, 2018; Emediato, 2008; Cavalcante, 2020) and in Critical Discourse Analysis with a sociocognitive aspect (Van Dijk 1997, 2020; Silveira, 2012; Amossy, 2020). The research has a theoretical-analytical procedure and a qualitative method with an interpretative basis. The analysis of the maximum grade texts indicates that the texts considered ENEM's maximum grade present the textual scheme of the dissertation of a thesis and fit in the dissertation-argumentative-explanatory concept and not in the dissertation-argumentative-opinionative one as expected/required by the referred exam